MicroRNA-21 mediated cross-talk between cardiomyocytes and fibroblasts in patients with atrial fibrillation - Pradhan, Kabita; Niehues, Paul; Neupane, Balram; Maleck, Carole; Sharif-Yakan, Ahmad; Emrani, Mahdi; Zink, Matthias Daniel; Napp, Andreas; Marx, Nikolaus; Gramlich, Michael (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrosis represents a major hallmark in disease progression of atrial fibrillation (AF). We have previously shown that circulating microRNA-21 (miR-21) correlates with the extent of left atrial fibrosis in patients undergoing catheter ablation for AF and can serve as a biomarker to predict ablation success. In this study, we aimed to validate the role of miR-21-5p as a biomarker in a large cohort of AF patients and to investigate its pathophysiological role in atrial remodeling. Methods For the validation cohort, we included 175 patients undergoing catheter ablation for AF. Bipolar voltage maps were obtained, circulating miR-21-5p was measured, and patients were followed-up for 12 months including ECG holter monitoring. AF was simulated by tachyarrhythmic pacing of cultured cardiomyocytes, the culture medium was transferred to fibroblast, and fibrosis pathways were analysed. Results 73.3% of patients with no/minor LVAs, 51.4% of patients with moderate LVAs and only 18.2% of patients with extensive LVAs were in stable sinus rhythm (SR) 12 months after ablation (p < 0.01). Circulating miR-21-5p levels significantly correlated with the extent of LVAs and event-free survival. In-vitro tachyarrhythmic pacing of HL-1 cardiomyocytes resulted in an increased miR-21-5p expression. Transfer of the culture medium to fibroblasts induced fibrosis pathways and collagen production. The HDAC1 inhibitor mocetinostat was found to inhibit atrial fibrosis development. Conclusion We validated miR-21-5p as a biomarker that reflects the extent of left atrial fibrosis in AF patients. Furthermore, we found that miR-21-5p is released in-vitro from cardiomyocytes under tachyarrhythmic conditions and stimulates fibroblasts in a paracrine mode to induce collagen production.